Experience of Developing a database of storytellers of the Yakut Epos - S. D. Lvova; L. N. Gerasimova (Научный диалог)
The results of the analysis of the basic principles of compiling the database “Olonkhosuts of Yakutia of the 17th—20th centuries” — about the storytellers of the Yakut national epic are presented. The relevance of the research is determined by some difficulties in the systematization and design of the information content of the repository. A brief overview of the history of the study of the personalities of Yakut storytellers is given, the stages of database development are discussed in detail. It is noted that as a result of the generalization of the material a reference book that contains more than 1300 names of storytellers of the 17th-20th centuries was published by the team of the Olonkho Research Institute of M. K. Ammosov North-Eastern Federal University. Problems identified in the process of filling in the cells are described. Particular attention is paid to entering data in the national language, their transliteration and translation into Russian. The definition of the types of the second names of olonkhosuts is given, the expediency of allocating a separate field for nicknames-pseudonyms reflecting the status and popular recognition of the talent of the narrator is substantiated. A sample database table on olonkhosuts is presented. As a result of the study, the parameters for selecting data for inclusion in the repository were compiled, the need for additional research work to identify the facts of the change of residence of olonkhosuts was determined, and recommendations were proposed for improving the principles of information content of the database.